answersLogoWhite

0


Best Answer

It is 2(2x+3) when factorised

User Avatar

Wiki User

โˆ™ 2018-02-06 14:17:19
This answer is:
๐Ÿ™
6
๐Ÿคจ
2
๐Ÿ˜ฎ
1
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards

J's study guide

2 cards

What is the name of Steve on minecraft's name

What is love

โžก๏ธ
See all cards

Steel Tip Darts Out Chart

96 cards

170

169

168

167

โžก๏ธ
See all cards
More answers
User Avatar

Farragh Comiskey

Lvl 2
โˆ™ 2021-02-09 14:35:50

10x

User Avatar

Add your answer:

Earn +20 pts
Q: How do you factorise 4x plus 6?
Write your answer...
Submit
Related questions

How do you factorise 4x plus 24?

4(x+6)


How do you factorise 24x plus 18?

It is: 6(4x+3)


How do you factorise 4x2 plus 5x - 6?

(4x-3)(x+2)


How do you factorise x squared plus 4x?

x2 + 4x = x(x + 4)


How do you factorise -9y-6 6xy 4x?

6xy+9y2


How do you factorise x2 plus 4x?

X2 + 4xx(x + 4)=======


How do you Factorise this 12xsquare-7x plus 1?

12x2 - 7x + 1 = 12x2 - 4x - 3x + 1 = 4x(3x - 1) - 1(3x - 1) = (3x - 1)(4x - 1)


How do you factorise x2-4x?

6


Factorise a a plus 10a plus 24?

(a + 6)(a + 4)


How do you factorise 8xยฒ-4xยฒ?

12


-6 plus 4x plus 9-2x?

-6 + 4x + (9-2x) = -6 + 4x + 9 - 2x = [ 3 + 2x ]


Combine 8x plus 5z minus 4x plus 3z plus 6?

8x + 5z - 4x + 3z + 6 = 8x - 4x + 5z + 3z - 6 = 4x + 8z - 6


How do you Factorise this 12x square 7x plus 1?

12x2 + 7x + 1 = 12x2 + 3x + 4x + 1 = 3x*(4x + 1) + 1*(4x + 1) = (4x + 1)*(3x + 1)


Factorise m squared plus 7m plus 6?

(m + 6)(m + 1)


-10x-6 plus 4x equals -4x plus 8?

-6x-6 -or- -6(x+1)


5x plus 7x-4x 6?

The answer to the math problem of 5x plus 7x-4x 6 is -12.


How do you factorise 3x plus 6?

It is: 3(x+2)


Why 4x plus 6 is the answer in x minus 5 plus 3x plus 11?

Because (x plus 3x) is 4x, and (-5 + 11) is 6.


What is 4x-5 plus 3y plus 4x-10y plus 11?

8x - 7y + 6


How tosolve 4x plus 2 plus 6 equals 2?

4x + 2 + 6 = 2 4x + 8 = 2 4x = -6 x = -6/4 = -3/2


What is -4x plus 5 plus 3x plus 6?

-4x + 5 + 3x + 6 = -x + 11


How do you factorise this expression - 2x plus 6?

2x + 6 = 2(x+3)


Factorise 5x squared plus 17x plus 6?

(5x + 2)(x + 3)


What is -4x plus 2-6?

It is -4x - 4


7x plus 6 minus 4x equals 5 plus 2x plus 7?

7x + 6 - 4x = 5 + 2x + 7 subtract 6 from both sides and combine the 5 and 7 on the right: 7x - 4x = 2x + 6 subtract 2x from both sides and combine the 7x and -4x on the left: x = 6